Factors affecting the effectiveness of quality control circles in a hospital using a combination of fuzzy VIKOR and Grey Relational Analysis - Mohammadkarim Bahadori; Ehsan Teymourzadeh; Foad Faizy Bagejan; Ramin Ravangard; Mehdi Raadabadi; Seyed Mojtaba Hosseini (Proceedings of Singapore Healthcare, 2018)
Background: One of the techniques used to achieve productivity, employees’ job satisfaction and higher quality goods and services, as well as to solve the problems by using a team, is the formation of quality control circles. Quality control circles enable managers to meet the organization’s and employees’ needs through making effective use of resources and facilities. On the other hand, the quality of services is always affected by uncertainty and ambiguous and implicit judgments, which make its measurement uncertain. Aim: The present study aimed to identify important factors affecting the effectiveness of quality control circles in a hospital, as well as rank them using a combination of fuzzy VIKOR and Grey Relational Analysis (GRA). Methodology: This was an applied, cross-sectional and descriptive–analytical study conducted in 2016. The study population consisted of five academic members and five experts in the field of nursing working in a hospital, who were selected using a purposive sampling method. Also, a sample of 107 nurses was selected through a simple random sampling method using their employee codes and the random-number table. The required data were collected using a researcher-made questionnaire which consisted of 12 factors. The validity of this questionnaire was confirmed through giving the opinions of experts and academic members who participated in the present study, as well as performing confirmatory factor analysis. Its reliability also was verified (α=0.796). The collected data were analyzed using SPSS 22.0 and LISREL 8.8, as well as VIKOR–GRA and IPA methods. Results: The results of ranking the factors affecting the effectiveness of quality control circles showed that the highest and lowest ranks were related to ‘Managers’ and supervisors’ support’ (Š = 6.80, R ~ = 0.36) and ‘Group leadership’ (Š = 2.63, R ~ = 0.98). Also, the highest hospital performance was for factors such as ‘Clear goals and objectives’ and ‘Group cohesiveness and homogeneity’, and the lowest for ‘Reward system’ and ‘Feedback system’, respectively. Conclusion: The results showed that although ‘Training the members’, ‘Using the right tools’ and ‘Reward system’ were factors that were of great importance, the organization’s performance for these factors was poor. Therefore, these factors should be paid more attention by the studied hospital managers and should be improved as soon as possible. Applying quality control circles in any organization is very helpful and provides opportunities for maximum use of employees’ creativity, initiative and skills in reaching their and their organization’s goals and objectives, and prepares favorable working conditions for the employees’ optimal performance through increasing the managers’ sense of responsibility and commitment.